Two new species of Chusquea (Poaceae, Bambuseae) from Northwestern Argentina - Guerreiro, Carolina Ines (2013)
Chusquea Kunth (Poaceae, Bambusoideae, Bambuseae) is the largest bamboo genus in the world. Approximately 13 species of Chusquea occur in the southern Andes of Argentina and Chile and all of them are endemic. In the present work, two new species found in high-altitude grasslands of the Andes mountain range in northwestern Argentina, Chusquea egluma and Chusquea floribunda, are described and illustrated. Morphological and anatomical characters are described and two identification keys for the Andean Chusquea species from northwestern Argentina are provided, one based on morphological characters (vegetative and reproductive), and the other on anatomical characters (culm and leaf epidermis and cross section). The new taxa and related species are compared in tables based on characters of taxonomic value.